Faire remonter les chiffres du Covid - Marine Boisson; Jérôme Denis (Revue d'anthropologie des connaissances)
The Covid-19 pandemic had a profound effect on the production and circulation of health data. This article examines the conditions under which, in France, a form of “upstreaming” of data towards the central administration was organised at the peak of the health crisis. It shows that this process of centralisation put the data and those responsible for it through three types of trial: infrastructural trials, relating to the capacity of the data to flow from one information system to another up to the central government departments; representational trials, relating to the way in which the data could correctly refer to the reality of the health crisis; and enunciative trials, arising from the tensions between the multiplicity of data and the uniqueness of their enunciating authority.